1991
DOI: 10.1007/bf00966700
|View full text |Cite
|
Sign up to set email alerts
|

Purification of endogenous inhibitors of [3H]flunitrazepam binding from bovine brain

Abstract: Endogenous substances which inhibited the binding of [3H]flunitrazepam ([3H]FNZ) to bovine synaptosomal membranes have been purified from the hot acetic acid extracts of the bovine brain. Three peaks of inhibitory activity were obtained by Sephadex G-10 gel chromatography. Two of the peaks (Peak 2, and Peak 3) which had lower molecular weights than that of peak 1 were identified as inosine and hypoxanthine by TLC methods. Another peak (Peak 1) was further purified to homogeneity using both cation and anion ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…The fact that only phosphocreatine-Mg-complex (acetate) was able to decrease this epileptic-like manifestation may indicate a different mechanism of action. Creatine binds to the benzodiazepine receptor [46], and one of us showed that high-dose creatine is able to slightly reduce population spike amplitude in brain slices [47]. Moreover, guanidino compounds (as creatine is) are known to interact with the GABA receptor [48].…”
Section: Discussionmentioning
confidence: 97%
“…The fact that only phosphocreatine-Mg-complex (acetate) was able to decrease this epileptic-like manifestation may indicate a different mechanism of action. Creatine binds to the benzodiazepine receptor [46], and one of us showed that high-dose creatine is able to slightly reduce population spike amplitude in brain slices [47]. Moreover, guanidino compounds (as creatine is) are known to interact with the GABA receptor [48].…”
Section: Discussionmentioning
confidence: 97%
“…Αυτή η υψηλή συγκέντρωση της κρεατίνης είχε κατασταλτικό αποτέλεσμα στην νευροδιεγερσιμότητα του εγκεφαλικού ιστού, που αναφέρθηκε για πρώτη φορά στην βιβλιογραφία [95]. Η κρεατίνη δεσμεύεται σε κάποιον βαθμό στον κεντρικό υποδοχέα των βενζοδιαζεπινών και ίσως αυτή η αλληλεπίδραση να παίζει κάποιο ρόλο στην κατασταλτική δράση της κρεατίνης σε υψηλές συγκεντρώσεις, αν και χρειάζεται περαιτέρω έρευνα για την εξήγηση της δράσης αυτής [96]. Η πρόληψη της μεταανοξικής υπερδιεγερσιμότητας του εγκεφάλου, με την υψηλή συγκέντρωση κρεατίνης μπορεί να εξηγηθεί μόνο εν μέρει από την άμεση κατασταλτική δράση της.…”
Section: κρεατίνη και επιληψίαunclassified